Human rights and sovereign standards in US security - Earnshaw, Sarah, author.
1 online resource (viii, 337 pages).
Keywords: "This book examines the history of human rights in US security imaginaries, and provides a a theoretical framework to explore the common-sense assumptions around US foreign relations and the universality of the human. The inability, or unwillingness, to provide fundamental freedoms is a central feature in the US presentation of postcolonial spaces as 'failed' and 'rogue' states: as nodes of disorder and instability, that are then subject to increasingly preemptive pacification. While largely focused on contemporary history from the post-WWII Universal Declaration to drone war, the author critically engages with longer, entwined histories such as Westphalian mythology, humanitarian intervention, and imperial aerial policing. Bridging history, law, politics, culture, and war, the theoretical bounding of the regime of truth offers a fresh reading for those knowledgeable on human rights and/as security policy. This volume will be of value to students and scholars of American Studies/history, critical IR, human rights history and those interested in conceptions of liberty and US foreign relations"--